Developing identities of STEM teachers at emerging STEM schools - Mohamed El Nagdi; Felicia Leammukda; Gillian Roehrig (SpringerOpen, 2018)
Abstract Background With the expansion of science, technology, engineering, and mathematics (STEM) schools all over the United States and the world, new roles for teachers are being created, and with these roles, identities are evolving. However, these roles and identities remain an ill-defined area in STEM. The purpose of this paper was to explore the developing STEM teachers' identities in emerging STEM schools, answering two research questions: (1) How do teachers define their roles as STEM teachers within a STEM school? (2) What do teachers identify as being important characteristics of STEM teachers? A multiple case study design was used to explore the research questions within a bounded context of two emerging STEM schools. Data for this study were drawn from semi-structured interviews conducted with eight teachers from two developing STEM schools within a large urban district in the Midwestern United States. Teams of teachers at each of the schools worked throughout the year to develop and implement their vision for STEM. Results Using an inductive data analysis process, three major themes that characterized a STEM teacher identity emerged. These were the unique nature of STEM teachers' identity; professional characteristics of STEM; and personal characteristics of STEM teachers. Collaboration, flexibility, awareness of students' needs, and advocates of equity and inclusion were identified as pivotal characteristics of STEM teachers. Conclusion This study concluded that STEM teachers' identity can be viewed as a dynamic, evolving process that results from the interaction of personal and professional traits within new educational experiences exemplified by the STEM endeavor in their schools. An alignment between teachers' personal philosophy and STEM understanding is essential for the success in teaching in STEM schools.